A Political Communication Analysis of Prabowo Subianto's First Official Speech - Ageng Soeharno; Mohammad Thamrin; Edhi Siswanto (POLITICO, 2025)
Political communication is a method used by political figures to convey messages to the public about power, government, and public policy in order to influence their beliefs, behavior, and attitudes toward politics in order to achieve specific political goals. Likewise, for a large country like Indonesia, the political communication of an elected and newly inaugurated president is a highly significant topic of discussion. As a country undergoing a presidential transition, the new president's welcome is likely to be crucial for the continuity of the nation and state within the Unitary State of the Republic of Indonesia. The words spoken by a president at his inauguration are invaluable for his future work plans after his inauguration. Some words carry profound meaning that deserve further study as lessons for all of us, so that the world knows that these words have significance as a president's work plan and work patterns in leading this great nation. Thus, the continuity of national life can be seen in President Prabowo Subianto's inaugural speech. Essentially, if we examine the speech closely, we will find many ambiguous sentences that require further study. In this article, all these ambiguous sentences will be studied and examined further so that their meaning is clear.